Evaluación técnico financiera de la implementación de una herramienta pulsante con la tecnología Powerwave para la estimulación en pozos inyectores del Campo la Cira Infantas (2016)
This project ís based on a pulsing tool implementation with powerwave technology at injector well Topilo X1 in La Gira Infantas Field, where there is a problem of low efficacy in the acid stimulation operations due to poor quality of the injection water, sediment accumulation, scales and fines migration in the near wellbore.